2016
DOI: 10.1080/09537104.2016.1203400
|View full text |Cite
|
Sign up to set email alerts
|

Inherited platelet dysfunction and hematopoietic transcription factor mutations

Abstract: Transcription factors (TF) are proteins that bind to specific DNA sequences and regulate expression of genes. The molecular and genetic mechanisms in most patients with inherited platelet dysfunction are unknown. There is now increasing evidence that mutations in hematopoietic TFs are an important underlying cause for defects in platelet production, morphology, and function. The hematopoietic TFs implicated in patients with impaired platelet function include runt related transcription factor 1 (RUNX1), Fli-1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…Consistent with the Gfi1b KO effect on megakaryopoiesis (20, 22, 23), different mutations in GFI1B are involved in platelet-related bleeding disorders (42). …”
Section: Platelet Deficiencies and Bleeding Disordersmentioning
confidence: 63%
“…Consistent with the Gfi1b KO effect on megakaryopoiesis (20, 22, 23), different mutations in GFI1B are involved in platelet-related bleeding disorders (42). …”
Section: Platelet Deficiencies and Bleeding Disordersmentioning
confidence: 63%
“…310 In 2013, Stockley et al . used next-generation sequencing (NGS) to analyze 13 unrelated patients suspected of having an inherited qualitative platelet defect in the UK Genotyping and Phenotyping of Platelets (UK-GAPP) study.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor RUNX1 plays a major role in hematopoiesis and megakaryopoiesis, and RUNX1 mutations are associated with familial thrombocytopenia, impaired platelet function and megakaryopoiesis, and a predisposition to acute myelogenous leukemia [13]. The mutation in most such patients is in the conserved DNA-binding RUNT domain [1, 2, 4].…”
Section: Introductionmentioning
confidence: 99%
“…A number of platelet abnormalities have been reported in patients with RUNX1 mutations, including a deficiency of granular content (storage pool deficiency, SPD) affecting dense granules (DG) and alpha granules, impaired aggregation, DG secretion, and protein phosphorylation [25]. In addition, abnormalities in mechanisms that regulate secretion have been reported in some patients [2, 3, 5], including in myosin light chain and pleckstrin phosphorylation, and decreased platelet PKC-θ [6, 7]. Platelet mRNA expression profiling of a patient with RUNX1 mutation [8] and other studies [7] have shown downregulation of several genes, including MYL9 , PRKQ ALOX12 and PF4, and some of these are direct transcriptional targets of RUNX1, providing evidence for aberrations in multiple platelets mechanisms, including in those regulating platelet responses to activation [2, 912].…”
Section: Introductionmentioning
confidence: 99%